Risk of multi-drug resistant Campylobacter spp. and residual antimicrobials at poultry farms and live bird markets in Bangladesh - Sucharit Basu Neogi; Md. Mehedul Islam; S. K. Shaheenur Islam; A. H. M. Taslima Akhter; Md. Mahmudul Hasan Sikder; Shinji Yamasaki; S. M. Lutful Kabir (BMC Infectious Diseases, 2020)
Abstract Background Understanding potential risks of multi-drug resistant (MDR) pathogens from the booming poultry sector is a crucial public health concern. Campylobacter spp. are among the most important zoonotic pathogens associated with MDR infections in poultry and human. This study systematically examined potential risks and associated socio-environmental factors of MDR Campylobacter spp. in poultry farms and live bird markets (LBMs) of Bangladesh. Methods Microbial culture and PCR-based methods were applied to examine the occurrence and MDR patterns of Campylobacter spp. in potential sources (n = 224) at 7 hatcheries, 9 broiler farms and 4 LBMs in three sub-districts. Antimicrobial residues in broiler meat and liver samples (n = 50) were detected by advanced chromatographic techniques. A questionnaire based cross-sectional survey was conducted on socio-environmental factors. Results Overall, 32% (71/ 224) samples were found contaminated with Campylobacter spp. In poultry farms, Campylobacter spp. was primarily found in cloacal swab (21/49, 43%), followed by drinking water (8/24, 33%), and meat (8/28, 29%) samples of broilers. Remarkably, at LBMs, Campylobacter spp. was detected in higher prevalence (p < 0.05) in broiler meat (14/26, 54%), which could be related (p < 0.01) to bacterial contamination of drinking water (11/21, 52%) and floor (9/21, 43%). Campylobacter isolates, one from each of 71 positive samples, were differentiated into Campylobacter jejuni (66%) and Campylobacter coli (34%). Alarmingly, 49 and 42% strains of C. jejuni and C. coli, respectively, were observed as MDR, i.e., resistant to three or more antimicrobials, including, tetracycline, amoxicillin, streptomycin, fluoroquinolones, and macrolides. Residual antimicrobials (oxytetracycline, ciprofloxacin and enrofloxacin) were detected in majority of broiler liver (79%) and meat (62%) samples, among which 33 and 19%, respectively, had concentration above acceptable limit. Inadequate personal and environmental hygiene, unscrupulously use of antimicrobials, improper waste disposal, and lack of health surveillance were distinguishable risk factors, with local diversity and compound influences on MDR pathogens. Conclusion Potential contamination sources and anthropogenic factors associated with the alarming occurrence of MDR Campylobacter, noted in this study, would aid in developing interventions to minimize the increasing risks of poultry-associated MDR pathogens under ‘One Health’ banner that includes poultry, human and environment perspectives.